Pengurangan Waktu Proses Pembuatan Produk Cap (C1805-009): Suatu Pendekatan Simulasi - Dhaul Fathoni; Johan Krisnanto Runtuk (President University, 2019)
PT.S is a metal pressing company that produces spare parts for the automotive industry. The increasing number of new companies, encouraging the company to make improvements continously, one of which is by reducing the processing time. The problem that occurs is the frequent occurrence of late pulling stocks in the finished product inventory area. One of them occurs in the Cap product (C1805-009) within a period of 6 months (October 2017 to March 2018) 16 times the stockout in the finished product inventory area. In addition, an increase in demand requires companies to do various ways, including adding four inspectors on each shift. This study aims to analyze the flow of production processes and waste of time with a simulation approach. Based on the simulation results using the Promodel software, it is known that the work station that is the cause of flow congestion is the inspection work station. Proposed improvements in simulation results also showed improvements, namely the reduction of processing time by 330.66% and the reduction in the number of operators by 50%. The simulation results can be considered by PT. S to improve the flow of the Cap product manufacturing process (C1805-009).